The two sides of the inclusive language - Carretero, Abigail; Medina Gómez, Lorena Y. (Opción, 2022)
This work explains what is meant by inclusive language, who promotes it, what it consists of and whether or not its use should be adopted. For the analysis, the visibility and neutralization strategies proposed by Escandell-Vidal (2019) are taken and complemented with the proposals of Bengoechea (2015), Bucio (2020), Guerrero (2020), López (s/f), Mendívil (2020), Parra (2021). A search was made in the oral and written record of Mexican Spanish in order to corroborate its use. It was found that there are still few occurrences of the strategies, we will have to wait to see if they dissipate or spread.